2018
DOI: 10.1016/j.watres.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium species and subtypes in animals inhabiting drinking water catchments in three states across Australia

Abstract: As part of long-term monitoring of Cryptosporidium in water catchments serving Western Australia, New South Wales (Sydney) and Queensland, Australia, we characterised Cryptosporidium in a total of 5774 faecal samples from 17 known host species and 7 unknown bird samples, in 11 water catchment areas over a period of 30 months (July 2013 to December 2015). All samples were initially screened for Cryptosporidium spp. at the 18S rRNA locus using a quantitative PCR (qPCR). Positives samples were then typed by seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 93 publications
1
51
0
Order By: Relevance
“…When samples from individual alpacas ( n = 18) from CsVIC25 were tested individually, C. cuniculus VbA25 was identified in a cria of 3.6 months of age; the gp60 sequence obtained (286 bp) (GenBank: MH356122) was 99% similar to the sequence with accession no. MG516794 from C. cuniculus VbA25 from a rabbit in Australia [22]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When samples from individual alpacas ( n = 18) from CsVIC25 were tested individually, C. cuniculus VbA25 was identified in a cria of 3.6 months of age; the gp60 sequence obtained (286 bp) (GenBank: MH356122) was 99% similar to the sequence with accession no. MG516794 from C. cuniculus VbA25 from a rabbit in Australia [22]. …”
Section: Resultsmentioning
confidence: 99%
“…The accurate detection and characterisation of eukaryotic microbes is central to determining their potential infection sources and transmission routes, particularly given that there are at least 37 described species of Cryptosporidium [2224], eight assemblages of Giardia duodenalis [25] and more than 200 genotypes of E. bieneusi [20] to discern. Therefore, the use of molecular (particularly PCR-based) methods has become crucial for any molecular epidemiological investigation [26].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, cryptosporidiosis affects a large number of animal species, including the main livestock animals such as: cattle, sheep, goats, pigs, rabbits, horses, donkeys, water buffalo, camels, and poultry [17] and zoonotic Cryptosporidium spp. have also been reported in wildlife species, including rabbits [18], deer [19], wild mammals [20], and fish [21].…”
Section: Disease In Livestockmentioning
confidence: 97%
“…A recent study in Australia showed the presence of zoonotic Cryptosporidium spp. in livestock and wild mammals in water catchments [20]. In addition, C. parvum has been detected in edible marine fish in European waters, indicating the extent of environmental contamination with this zoonotic pathogen [21].…”
Section: Transmission Of Cryptosporidiummentioning
confidence: 99%
“…To date, at least 39 species of Cryptosporidium have been identified [13][14][15][16], and at least 21 species are considered zoonotic, among which C. hominis and C. parvum are the two main pathogens causing cryptosporidiosis in humans [17]. However, in recent years, with the development of molecular biological technologies, the number of cryptosporidiosis cases confirmed to be caused by other Cryptosporidium species has increased, and some species or genotypes are predominant in specific countries or regions.…”
mentioning
confidence: 99%